2015
DOI: 10.1021/jacs.5b03818
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Transient Surface Species during Ge Nanowire Growth and Their Influence on Growth Stability

Abstract: Surface adsorbates are well-established choreographers of material synthesis, but the presence and impact of these short-lived species on semiconductor nanowire growth are largely unknown. Here, we use infrared spectroscopy to directly observe surface adsorbates, hydrogen atoms and methyl groups, chemisorbed to the nanowire sidewall and show they are essential for the stable growth of Ge nanowires via the vapor-liquid-solid mechanism. We quantitatively determine the surface coverage of hydrogen atoms during na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 43 publications
4
50
0
Order By: Relevance
“…The primary effects are due to (1) changes in supersaturation with dopant introduction and/or (2) changes to the NW surface energy due to the dopant precursor or its decomposed by-products. 49 It has been reported that the Si NW nucleation could be completely inhibited with high phosphine-to-silane ratios, 50 and similar results were also observed in arsine (AsH3) 51 or trimethylantimony (TMSb) 52 doped Si NWs.…”
Section: Influence Of Doping On Nanowire Growth Ratementioning
confidence: 52%
“…The primary effects are due to (1) changes in supersaturation with dopant introduction and/or (2) changes to the NW surface energy due to the dopant precursor or its decomposed by-products. 49 It has been reported that the Si NW nucleation could be completely inhibited with high phosphine-to-silane ratios, 50 and similar results were also observed in arsine (AsH3) 51 or trimethylantimony (TMSb) 52 doped Si NWs.…”
Section: Influence Of Doping On Nanowire Growth Ratementioning
confidence: 52%
“…[29][30] The 〈110〉 growth direction of small diameter group IV NWs has been attributed to energy contributions of side facets; [31][32] however, the contributions of side-wall adsorption of decomposition products cannot be ruled out and variations of adsorbates on side facets have been described to cause changes in growth direction. [33][34][35] Therefore, the changes in growth direction with temperature cannot be assigned unequivocally to size effects, even though the same DPG precursor results in different preferred growth directions upon changes in NW diameter. 30 EDX-maps for these NWs do not show any preferential Ga incorporation in the NWs (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to controlling the surface roughness of the nanowire boundaries, surface chemistry provides another mechanism to engineer phonon scattering at the boundaries and control the thermal conductivity of nanowires [115]. It was observed that HF etching followed by surface hydrogenation could provide nanowires with higher thermoelectric efficiency due to reduced thermal conductivities via boundary impurities [116].…”
Section: Surface Chemistrymentioning
confidence: 99%